The experience of nicotine dependence among adolescent smokers - Nurvita Risdiana; Yanuar Fahrizal; Wahyulianto Wahyulianto (Intelektual Pustaka Media Utama, 2022)
A cigarette contains nicotine substance that can cause smokers to become dependent on nicotine. Smokers who are already addicted will experience withdrawal syndrome. The earlier age people smoke at, the higher level of dependence they have. The adverse effect of nicotine dependence is that smokers will find it difficult to stop smoking. This study aimed to investigate the experiences of adolescent smokers who are dependent on nicotine. This was a qualitative study conducted with a phenomenological approach. Data were collected through an in-depth interview with five informants who were selected through purposive sampling technique. Triangulation was employed to enhance the credibility of the study. Data were analyzed using a phenomenological approach. This study resulted in four main themes, namely: age to start smoking; the causes of smoking; perceptions of smoking; experience of smoking cessation. Conclusion that can be drawn for this study was smoking abstinence led to anxiety, decreased concentration and craving to cigarette. The smokers need to educate about the nicotine withdrawal symptoms that they can anticipate it when symptoms appeared.